Devising New CLA Methodology in Teaching Programming Using Flipped Learning with Counterpart Learner Assistant - CLA - Majlinda Fetaji; Abdulmelih Gylcan; Bekim Fetaji; Mirlinda Ebibi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
The focus of the research study is to devise a new CLA methodology in teaching programming using flipped learning using a counterpart learner assistant -CLA from the learner side. Investigated the benefits of the flipped learning pedagogy focusing on assessment of learners on their attitudes, motivation, and effectiveness when using flipped learning compared with traditional classroom learning has been realized. There is a difference between a Flipped Classroom and Flipped Learning. These terms are not interchangeable. Flipping a class can, but does not necessarily, lead to Flipped Learning. Four broad categories of instructional approaches for use in an flipped learning have been identified: (a) individual activities, (b) paired activities, (c) informal small groups, and (d) cooperative student projects. The research study is based on the theory of Bloom's revised taxonomy of cognitive domain. This taxonomy provides six levels of learning discussed in the research methodology section. In order to analyse all this, a case study experiment was realized and insights as well as recommendations are presented.
Keywords: A23; 330; flipped classroom; programming robotics; effectiveness of learning; flipped learning paradigm